Determinant of indonesian commodity coffee export In the era of covid-19 pandemic - Erlambang Budi Darmanto; Suhartono Suhartono; Yunita Satya Pratiwi; Moh. Adenan (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This study aims to analyze the factors of gross domestic product, total consumption, exchange rate, and export goods price index on export performance of coffee beans after pandemic Covid-19. This study uses secondary data and (Generalized Method of Moment). The study shows that the variable total consumption and value of exports show a positive and insignificant relationship and the variables of GDP and exchange rates show a negative and significant relationship with coffee commodity exports with exports of coffee commodities.